Integrability of doubly-periodic Riccati equation - Ma Ling; Guan Ke-Ying (International Journal of Mathematics and Mathematical Sciences)
By the structure of solvable subgroup of SL(2,ℂ) (see [1]), the integrability and properties of solutions of a Riccati equation with an elliptic function coefficient, which is related to a Fuchsian equation on the torus T2,is studied.